Can engagement and performance be improved through online training on emotional intelligence? A quasi-experimental study - Junça Silva, A.; Almeida, N. (International Journal of Educational Management, 2023)
Purpose: Online learning is an effective training strategy to help students, as one of the success factors is academic engagement. Therefore, the use of online training courses to influence academic engagement and performance in emotional intelligence learning experiences is worthy of investigation. This study explores the influence of emotional intelligence as an online training course and its impact on academic engagement and learning outcomes - performance. Methodology: We used a quasi-experimental study with two groups of participants who were randomly assigned (experimental e control) and with pretest-posttest measurements of the online training. The emotional intelligence online training (for the experimental group) was conducted during a single semester, with eight hours of training. The methodology of reflective, role-playing, case study and group work was followed. Measurements of student academic engagement and emotional intelligence were collected before (one week before the training) and after the intervention (on the last training session). Performance was measured after the intervention. Findings: The mean scores improved for all the variables, with the differences being statistically significant. The students assessed their learning positively. The results also showed that emotional intelligence was positively related to academic engagement but not to performance. This means that emotional intelligence training was effective in increasing the academic engagement of university students. Implications: The results are promising in terms of the students retaining the competencies acquired. Therefore, this type of online training is recommended for the emotional intelligence and academic engagement of future human resources professionals. Moreover, according to the results, it would be possible to use emotional intelligence training programs in schools, besides other programs, to promote the academic engagement and performance of students. Originality: The design of the study provides evidence that is an added value for higher education institutions.